Conditions of the Local Green Economy in the Period 2010-2020 - Pawlik, Andrzej; Dziekański, Paweł (Uwarunkowania lokalnej zielonej gospodarki w latach 2010-2020, 2023)
The green economy is an important tool for ensuring sustainable development, and is characterised by a high quality of life for the population, along with careful and rational use of natural resources. The aim of the article was to analyse the spatial differentiation of the green economy in 2010-2020. The research used a synthetic measure that allows for the studied districts to be ranked and grouped according to the main criterion, as well as investigating whether and to what degree the variables determine differentiation in the green economy. In order to achieve this aim, the authors used the following research methods: analysis of the subject literature, followed by statistical analysis using a synthetic measure. To construct the synthetic measure, the Technique for Order Preference by Similarity to an Ideal Solution method was used. The research results present the spatial differentiation of the selected districts in the period 2010-2020.
Biblioteka Regionalisty = Regional Journal, 2023, Nr 23, s. 84-95
Keywords: green economy; spatial differentiation; synthetic measure; zielona gospodarka; zróżnicowanie przestrzenne; miara syntetyczna